1990
DOI: 10.1002/jsfa.2740530409
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of lipid in the maillard reaction between cysteine and ribose: The effect of a triglyceride and three phospholipids on the volatile products

Abstract: The inclusion of phospholipid in the Maillard reaction between cysteine and ribose is known to modify the volatile aroma compounds produced. The contributions made to the headspace volatiles by 60 major products of this reaction have been compared for four digerent lipids and their effect on aroma quality noted.The results described demonstrate marked dissimilarities between the behaviour of the four lipids. The most noticeable distinction was between the effect of triglyceride and the three phospholipids, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 28 publications
5
62
0
Order By: Relevance
“…The sulphurs in heterocyclic sulphur compounds like thiazoles (roasted meaty odours) may be derived from amino acids (cysteine, cystine and methionine) or from thiamine (Girand & Durance, 2000). The formations of some of those compounds have been shown to depend on pH and these may explain the known pH dependency of meaty flavours (Farmer & Mottram, 1990). In the present study, 3-(methylthio) propanal (methional), the Strecker aldehyde of methionine, has been detected in most of the miso samples.…”
Section: Resultsmentioning
confidence: 97%
“…The sulphurs in heterocyclic sulphur compounds like thiazoles (roasted meaty odours) may be derived from amino acids (cysteine, cystine and methionine) or from thiamine (Girand & Durance, 2000). The formations of some of those compounds have been shown to depend on pH and these may explain the known pH dependency of meaty flavours (Farmer & Mottram, 1990). In the present study, 3-(methylthio) propanal (methional), the Strecker aldehyde of methionine, has been detected in most of the miso samples.…”
Section: Resultsmentioning
confidence: 97%
“…The methods used for the extraction and analysis of these lipids have been described previously (Farmer and Mottram 1990 (Farmer and Mottram 1990). " Presumcd to arisc from plasmalogens.…”
Section: Methodsmentioning
confidence: 99%
“…ammonia, hydrogen sulphide, is an important pathway for heterocyclic compounds associated with typical flavours (thiazoles, pyridine, thiophenes, oxazoles and other heterocyclics) (Zamora, Alaiz, & Hidalgo, 2000). Farmer and Mottram (1990) reported that (E,E)-2,4-decadienal was a possible precursor of 2-pentylpyridine that had been identified in tallow. Mottram (1985) found some heterocyclic compounds with long n-alkyl substituents present in meat, like butyl and pentyl pyrazines; it has been found that these compounds could result from the reaction of pentanal or hexanal with a dihydropyrazine, formed by the condensation of two aminoketone molecules.…”
Section: Volatile Compounds Identified In the Headspace Of Oxidised Tmentioning
confidence: 99%